A Cross Sectional Study of Deaths Due to Snakebite: Autopsied at a Tertiary Care Centre, Hubballi - Mahesh M Devadas; Vijay N Tasgaonkar; Suresh Kumar Karthikean; Anand Patil (Institute of Medico-legal Publications Pvt Ltd, 2021)
Worldwide, Snakebite is an important and preventable health hazard in many of the tropical and subtropicalcountries. Death following snake bite is a cumulative effect of all the toxic reactions that are producedby the snake venom in the body of the victim.1Globally it is estimated that the true incidence of snakeenvenomation could exceed 3 million per year and about 1,00,000 of these develop severe sequelae. Withthis background, a study has been conducted to determine the pattern of snakebite death cases, autopsied atKIMS, Hubballi, Karnataka. The study revealed that maximum number of snakebite cases were recorded inthe rainy season (34.9%) followed by the winter season (31.7%).In a greater number of cases the incidenceof snake bite occurred predominantly in lower limb (54%) as compared to upper limb (46%).Peak incidenceof snake bite was recorded in the time between 08:00 am to 04:00 pm (41.3%) followed by 04:00 pmto midnight (30.2%). Majority of the cases were declared dead (47.61%) within 24 hours of initiation ofanti-snake venom. The cause of death in majority of the study population was respiratory failure (92.06%)followed by shock (7.93%).